A Birds-Eye (Re)View of Acid-Suppression Drugs, COVID-19, and the Highly Variable Literature - Mura, Cameron; Preissner, Saskia; Preissner, Robert; Bourne, Philip E. (Frontiers in Pharmacology, 2021)
This Perspective considers the surge of information on the potential benefits of acid-suppression drugs in the context of COVID-19, with an eye on the variability (and confusion) across the reported findings--at least as regards the popular antacid famotidine. The inconsistencies reflect conflicting conclusions from independent clinical-based studies that took roughly similar approaches, in terms of study design (retrospective, cohort-based, etc.) and statistical analyses (propensity-score matching and stratification, etc.). The contradictions have significant ramifications in choosing therapeutic interventions: e.g., do potential benefits of famotidine indicate its use in a particular COVID-19 case? Beyond this vital therapeutic issue, conflicting information on famotidine must be resolved before its integration in ontological and knowledge graph-based frameworks, which in turn are useful in pharmacological drug repurposing efforts. To begin systematically structuring the rapidly accumulating findings, in the hopes of clarifying and reconciling discrepancies, we consider the information along three proposed 'axes': (i) a context-of-disease axis, (ii) a degree-of-[therapeutic]-benefit axis, and (iii) a mechanism-of-action axis. We suspect that incongruities in how these axes have been (implicitly) treated has impacted the confusion regarding famotidine and COVID. We also trace the evolution of information on acid-suppression agents as regards transmission, severity, and mortality of COVID, given the many literature reports that have accumulated. By grouping the studies conceptually and thematically, we identify three eras in the progression of our understanding of famotidine and COVID. Harmonizing these findings is a key goal for both clinical standards-of-care (COVID and beyond) as well as ontological and knowledge graph-based approaches.